mGlu(5) receptors are involved in the discriminative stimulus effects of self-administered ethanol in rats - Besheer, Joyce (2006)
Recent work has identified a role for metabotropic glutamate receptor subtype 5 (mGlu(5)) in the discriminative stimulus properties of investigator-administered ethanol. The purpose of this study was to determine if mGlu(5) receptors modulate the discriminative stimulus properties of self-administered ethanol. Results show that the mGlu(5) receptor antagonist 6-Methyl-2-(phenylethynyl)pyridine (MPEP; 10 mg/kg) inhibited the discriminative stimulus properties of consumed ethanol during a self-administration test session. Further, 10 mg/kg MPEP increased and 1 mg/kg MPEP decreased the amount of self-administered ethanol required to produce full substitution. These results indicate that mGlu(5) receptors are involved in the expression of the discriminative stimulus properties of self-administered ethanol.